Sharing hard labour: developing a standard template for data summaries in guideline development. Issue 2 (5th January 2011) - Mlika-Cabanne, N; Harbour, R; de Beer, H; Laurence, M; Cook, R; Twaddle, S
Abstract : Background: A key objective of the Guidelines International Network (GIN) is to reduce duplication of effort. To address this objective, a working group was established to define a minimum dataset for inclusion in all evidence tables. Methods: A literature review was conducted to identify existing evidence tables, and GIN member organisations were asked to provide the tables they use. The results were used to develop a minimum dataset (template) for studies addressing intervention questions. The template was pilot-tested by a group of guideline developers and reviewed at GIN conferences. Results: The literature search yielded 65 articles. These dealt with reporting standards and trial quality (eg, CONSORT statement) rather than which data should be extracted from studies. However, the checklist items given were considered useful. Nineteen GIN members provided evidence tables; 17 tables were used for analysis. The number of items included in the tables ranged from 8 to 19, with several items common to all tables. Within individual items, the level of detail varied widely. The draught template included a majority of items relating to objective data. Pilot testing revealed that the median time to read a paper and complete the template was 2 h for a randomised controlled trial and 2½ h for a non-randomised, controlled intervention study. The median rating for both relevance and clarity of items was high. Conclusion: The template listing the items needed to summarise an interventional study is now available for large-scale testing by all organisations.